(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
According to the historical context of technological society, it seems urgent to consider the unusual scope and the ethical issues raised by the present technological provocation, which lead to questioning the productive provocation which man exerts over nature. Nevertheless before such questioning takes place, it is necessary to access the primary essence of technique. This paper sets a path for the comprehension of technique starting from the meaning of po…hsij based on Plato’s ideas. In his work "Symposium", technique emerges as tšcnh, which instead of exerting a provocative production, depends on the provocation of nature.